Written corrective feedback: preferences and justifications of teachers and students in a Thai context - Black, Douglas Aaron; Nanni, Alexander (Penerbit Universiti Kebangsaan Malaysia, 2016)
This study investigates the preferences and justifications of teachers and students on written corrective feedback (WCF) at a tertiary institution in Thailand and is aimed at expanding on prior similar studies conducted with smaller data sets in different contexts. Quantitative and qualitative questionnaire data were collected from 262 intermediate students and 21 teachers in order to test two hypotheses: (1) teachers’ and students’ WCF preferences would differ significantly, and (2) their justifications for their preferences would differ significantly. The hypotheses were confirmed: teachers rated indirect feedback with metalinguistic comment as being most useful while students most preferred direct feedback with metalinguistic comment. This trend extended to all types of direct feedback being preferred by students while teachers preferred all types of indirect feedback. The most common explanation for the teachers’ preferences was the development of metacognitive skills, while accuracy was the greatest concern for students. The pedagogical implications of the results regarding expectations, student agency, and self-efficacy are discussed.